Costs of Joint Replacement in Osteoarthritis: A Study Using the National Joint Registry and Clinical Practice Research Datalink Data Sets. Issue 3 (13th January 2022) - Leal, Jose; Murphy, Jacqueline; Garriga, Cesar; Delmestri, Antonella; Rangan, Amar; Price, Andrew; Carr, Andrew; Prieto‐Alhambra, Daniel; Judge, Andrew
Abstract : Objective: To estimate the costs of primary hip and knee replacement in individuals with osteoarthritis up to 2 years postsurgery, compare costs before and after the surgery, and identify predictors of hospital costs. Methods: Patients age ≥18 years with primary planned hip or knee replacements and osteoarthritis in England between 2008 and 2016 were identified from the National Joint Registry and linked with Hospital Episode Statistics data containing inpatient episodes. Primary care data linked with hospital outpatient records were also used to identify patients age ≥18 years with primary hip or knee replacements between 2008 and 2016. All health care resource use was valued using 2016/2017 costs, and nonparametric censoring methods were used to estimate total 1‐year and 2‐year costs. Results: We identified 854, 866 individuals undergoing hip or knee replacement. The mean censor‐adjusted 1‐year hospitalization costs for hip and knee replacement were £7, 827 (95% confidence interval [95% CI] 7, 813, 7, 842) and £7, 805 (95% CI 7, 790, 7, 818), respectively. Complications and revisions were associated with up to a 3‐fold increase in 1‐year hospitalization costs. The censor‐adjusted 2‐year costs were £9, 258 (95% CI 9, 233, 9, 280) and £9, 452 (95% CI 9, 430, 9, 475) for hip and knee replacement, respectively. Adding primary and outpatient care, the mean total hip and knee replacement 2‐year costs were £11, 987 and £12, 578, respectively. Conclusion: There are significant costs following joint replacement. Revisions and complications accounted for considerable costs and there is a significant incentive to identify best approaches to reduce these.